PERAN MEDIA SOSIAL DALAM MEMBENTUK SIKAP ANTI PERUNDUNGAN PADA REMAJA - Sutrisna, Doda; Gustania, Ristia; Supriatna, Yusuf; Wasliman, Eva Dianawati; Wasliman, Iim (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This research aims to explore the role of social media in shaping anti-bullying attitudes among adolescents, with a focus on a case study conducted at SMP Negeri 14 Kota Bandung. The research adopts a qualitative approach with a case study design, involving in-depth interviews, observations, and social media content analysis. The results indicate that social media plays a significant role in shaping anti-bullying attitudes among adolescents. Content that supports positive norms, educates about the impact of bullying, and engages in anti-bullying campaigns through social media can positively influence adolescent attitudes. However, social media can also become a platform for bullying if not monitored closely, with the presence of negative content and online bullying behaviors. This research provides a profound understanding of the complexity of the role of social media in shaping anti-bullying attitudes among adolescents, serving as a foundation for the development of more effective educational programs to reduce bullying among adolescents, especially within the school environment.